Dataset: Compositional analysis and hydrothermal liquefaction of a high-ash microalgae biofilmMendeley Data - Jacob D. Watkins; Hamza Abdellaoui; Elise Barton; Clayton Lords; Ronald C. Sims (Data in Brief)
This dataset contains biochemical composition data and hydrothermal liquefaction (HTL) yield results for a high-ash microalgae biofilm which was cultivated in effluent from a mesophilic anaerobic digester using polyethylene rotating algae biofilm reactors (RABRs). These data were originally collected for use in a techno-economic analysis of biocrude, biodiesel, and bioplastic production from algae that was cultivated using RABRs for municipal wastewater reclamation.Biochemical data for the microalgae biomass includes bulk protein, measured both using the Bradford protein assay and by multiplying total N; carbohydrate content, measured using a 3-methyl-2-benzothiazolinone hydrazone / dithiothreitol (MBTH/DTT) assay; total lipid content, measured using a sulpho-phospho-vanillin method; hexane-extractable lipid content, measured by mass difference after extraction with methanol and hexane; ash content, measured by mass difference after incineration at 550°C; moisture content of the harvested biofilm slurry, measured by mass difference after drying at 60°C, mineral composition, measured using an inductively-coupled plasma spectrophotometer; higher heating value, measured using a bomb calorimeter; and CHNS-O elemental composition, measured using an elemental analyser.Data reported for the HTL product phases include mass yields for each phase (solid, aqueous, biocrude, gas); higher heating value of the biocrude phase, measured using a bomb calorimeter; elemental composition of the biocrude phase, measured using an elemental analyzer; and chemical properties of the aqueous phase, including pH, chemical oxygen demand (HACH method 8000), total nitrogen (HACH method 10,208), total ammonia (HACH method 10,301), total phosphorus (HACH method 10,209/10,210), and total organic carbon (HACH method 10,267).Currently, the effects of ash composition and HTL heating rate on biocrude yields and on N and P partitioning into biocrude, aqueous, and solid phases are not clearly defined. Models used to predict biocrude yields after HTL of microalgae are commonly trained using data collected from numerous studies. This dataset contains the feedstock composition data and ramp rate data necessary to help define the effects of ash content on biocrude yields after HTL and can be reused to help train yield-prediction models for the HTL of microalgae and other feedstocks.